Dampak Teknologi terhadap Pembelajaran di Abad 21 - Budiyono, Slamet; Haerullah, Haerullah (TSAQOFAH, 2024)
The progress of the education sector in the modern 5.0 era presents significant challenges and opportunities. This article reviews the positive and negative impacts of technology on 21st-century education and efforts to optimize its usage. The research methodology employed is qualitative descriptive, involving the exploration of learning and educational technology definitions and the analysis of technology's impact on 21st-century learning. Research findings indicate that technology facilitates information access, creates new learning methods, and enhances data processing efficiency. However, there are also negative impacts such as dependence on technology, cybercrime risks, and a decline in ethics and social interaction. The conclusion emphasizes the importance of collaboration among educational institutions, technology industries, and governments to strengthen technological literacy, develop competency-based curricula, ensure adequate infrastructure, and monitor and evaluate the effectiveness of technology-based learning. Recommendations for optimizing technology in 21st-century education include training for educators and learners, parental supervision reinforcement, promotion of interdisciplinary learning, and regular updates in teaching methods. With this approach, educational institutions are expected to be more effective in addressing challenges and leveraging opportunities offered by the 21st-century education era, thus preparing a generation ready to compete on the global stage.